Sustainable tourism: analysis of methods and applications in the Indonesian tourism journals - Agung Yoga Asmoro; Hery Sigit Cahyadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study departs from an observational study of sustainable tourism research articles published in the Indonesia tourism journals, which was analyzed by content analysis. This study aims to get a complete picture of what and how the manifestation of sustainable tourism research articles in Indonesia has been carried out, especially in methods and its applications. The authors found that tourism journals only occupied a small fraction (0.43%). Twenty-six tourism journals and 304 articles were identified. This study found that most methods used by sustainable tourism researchers generally replicate existing methods; there has been rarely development and or innovation of research methods. Qualitative research far outperforms quantitative and mixed methods, where descriptive qualitative research is the most significant. The application of the study is relatively evenly distributed on the dimensions of sustainable tourism and geographic area, but less on stakeholders and management functions. The authors conclude that the trend of sustainable tourism research published in Indonesian tourism journals is increasing. Tourism researchers are scattered from various parts of Indonesia, but tourism journals in Indonesia have not been able to attracted significant interest of the international research community yet. There has never been an assessment of the journal's methods and applications for sustainable tourism research in Indonesia. Therefore, this paper is beneficial as a reference for sustainable tourism researchers in the future.